Implementation of Problem-Based Learning Model to Improve Reading Comprehension Skills of Fourth-Grade Students at Kristen Patti Elementary School - Warsoy, Leonora; Notanubun, Zainuddin; Kilikily, Cristianti Costafina (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
Reading comprehension among Indonesian elementary school students remains critically low, as evidenced by the 2022 PISA results showing a literacy score of 359 points, significantly below the OECD average of 476 points. A similar condition was identified among fourth-grade students at Kristen Patti elementary school, where only 11% of students met the minimum completeness criteria during initial assessment, with a class average of 65. Conventional teacher-centered and passive learning methods have been identified as contributing factors to low reading literacy. This study aimed to examine the effectiveness of implementing the Problem Based Learning model in improving reading comprehension skills of fourth-grade students at Kristen Patti elementary school. This classroom action research employed the Kemmis and Taggart model, conducted over two cycles with 27 students as research subjects. Data were collected through written tests and observations, while quantitative descriptive statistics were utilized for data analysis. The findings revealed significant improvements in learning completeness percentages, increasing from 11% during the pre-action stage to 48% in Cycle I and reaching 93% in Cycle II. The class average score also rose from 65 to 81. In conclusion, the Problem Based Learning model proved effective in enhancing reading comprehension skills of fourth-grade students at Kristen Patti elementary school.